Imaging Metabolic Flow of Water in Plants with Isotope‐Traced Stimulated Raman Scattering Microscopy - Simin Bi; Jianpeng Ao; Ting Jiang; Xianmiao Zhu; Yimin Zhu; Weibing Yang; Binglian Zheng; Minbiao Ji (Advanced Science)
Abstract Water plays a vital role in the life cycle of plants, participating in various critical biochemical reactions during both non‐photosynthetic and photosynthetic processes. Direct visualization of the metabolic activities of water in plants with high spatiotemporal resolution is essential to reveal the functional utilization of water. Here, stimulated Raman scattering (SRS) microscopy is applied to monitor the metabolic processes of deuterated water (D2O) in model plant Arabidopsis thaliana (A. thaliana). The work shows that in plants uptaking D2O/water solution, proton‐transfer from water to organic metabolites results in the formation of C‐D bonds in newly synthesized biomolecules (lipid, protein, and polysaccharides, etc.) that allow high‐resolution detection with SRS. Reversible metabolic pathways of oil‐starch conversion between seed germination and seed development processes are verified. Spatial heterogeneity of metabolic activities along the vertical axis of plants (root, stem, and tip meristem), as well as the radial distributions of secondary growth on the horizontal cross‐sections are quantified. Furthermore, metabolic flow of protons from plants to animals is visualized in aphids feeding on A. thaliana. Collectively, SRS microscopy has potential to trace a broad range of matter flows in plants, such as carbon storage and nutrition metabolism.